Molecular Phylogenetics and Comparative Examination of Voucher Museums Reveal Two New Species of Gymnophthalmid Lizards (Squamata, Gymnophthalmidae) from the Peruvian Andes, with Comments on Proctoporus guentheri (Boettger, 1891) - Luis Mamani; Roxana Cruz; Sergio Mallqui; Alessandro Catenazzi (Diversity, 2022)
The genus Proctoporus comprises cursorial and semifossorial lizards that inhabit the Andes of Argentina, Bolivia, and Peru. The taxonomy is complex, and many undescribed species and geographic gaps remain to be addressed. In this study, we use molecular phylogenetics and examine voucher museums to describe two new species of gymnophthalmid lizards from the montane forests of Cusco, on the eastern slopes of the Andes of Peru. We inferred phylogenetic relationships from concatenated sequences of four mitochondrial (12S, 16S, ND4, and Cytb) and one nuclear (c-mos) gene fragments, using a Maximum Likelihood approach and Bayesian Inference. We also examined and compared meristic traits of the specimens deposited in herpetological collections in Peru and Bolivia. Our molecular phylogeny had strong support for the monophyly of the subfamily Cercosaurinae, low support for the genus Proctoporus, and revealed two new taxa of Proctoporus. The two new species, which we name P. katerynae sp. nov. and P. optimus sp. nov., are characterized as having two rows of pregular scales and three anterior infralabials. Furthermore, we re-identified specimens assigned to P. laudahnae as P. guentheri, and we comment on the taxonomy of P. guentheri. Finally, we discuss how global climate change and human-caused habitat loss may threaten P. katerynae sp. nov. and P. optimus sp. nov. by the mechanism known as “Escalator to extinction”.